ANALISIS AKSESIBILITAS PERMODALAN USAHA MIKRO KECIL PADA LEMBAGA KEUANGAN FORMAL DI PROVINSI SUMATERA BARAT - Rita Diana (Jurnal Ekonomi dan Pembangunan, 2025)
Small Micro Enterprises (MSEs) are populist businesses that have the potential to continue to be developed. To develop the business, MSEs should increase the product capacity needed so that it is requiring much capital. Lack of capital and the ability and knowledge MSE managers make MSEs unable to keep up with changes in customer satisfaction and global competitiveness. The purpose of this study is to analyze the factors that influence the low access of MSEs to capital resources in West Sumatra Province using the logistic regression method. The results of the study indicate that MSEs incorporated in cooperatives have three times greater opportunities to gain access to capital from formal financial institutions compared to businesses that are not members of cooperatives. MSEs that have a business development plan is twice as likely than other businesses that do not have a development plan can access capital from formal financial institutions. From the results, it can be seen from MSEs whose managers are male, less education than high school, locations in rural areas, that work more than five years and have more money to get funds from formal financial institutions.